Saturday

April 19, 2014

April 19, 2014

Posted by **meherin** on Wednesday, July 23, 2008 at 1:05pm.

Ex. (-6)-(-41)+(-18)-35

= -6+41-18-35=35-18-35=-18

i understand that part

how do you do this two?

(-2)-(-6)-4= -2+6-4=-_+6=

-48+(-25)-(-13)+12=

in the first problem, there is a blank that u have to fill in first

help me please

- math -
**Damon**, Wednesday, July 23, 2008 at 1:36pm(-2)-(-6)-4= -2+6-4=-_+6=

-2-4 = -6

so

-6+6 = 0

in other words

(-2)-(-6)-4= -2+6-4=-6+6= 0

================================

-48+(-25)-(-13)+12= - 48 - 25 + 13 + 12

**Related Questions**

Math - What is 35 13/18 - 24 7/18 (by the way 13/18 and 7/18 are fractions)? Am ...

algbrea - 3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -12x -...

algebra - This is how my book shows it, but I don't know solve the equation by ...

math - would someone check these please 1. find the square root of 25 answer 5 2...

physics - 1. Two identical 15.0 kg balls, each 25.0 cm in diameter, are ...

Algebra - I need help with my daughters homework. I know a little bit of algebra...

Math - 23.At Thursday's volleyball game there 4 fans from Hudson for every 5 ...

math115 - add -57+(-22)=-79 place numbers in acsending order 25,-13,8,-2,13,3,18...

math115 - add -57+(-22)=-79 place numbers in acsending order 25,-13,8,-2,13,3,18...

math - Find and Interpret the median and the interquartile range for each ...